Campus to Corporate : Your Roadmap to Employability - Joshi, Gangadhar (Los Angeles SAGE Publications, 2015)
Insights into the basic skills required to cope with requirements of corporate life.
Include Index
Keywords: India -- Career development -- College graduates--Employment